Integration of a power thermal plant under operation to a biomass gasification system: An approach through sensitivity analysis and optimization procedure - de Paula, Isabele Oliveira [UNESP]; Salviano, Leandro Oliveira [UNESP] (My University, 2025)
In light of current energy and environmental challenges, such as significant carbon emissions from fossil fuels and the resulting global warming, there is an urgent need to transition away from traditional energy generation methods. One promising alternative is biomass gasification, particularly when integrated into existing power plants, such as natural gas-fired generation systems. This study presents a thermodynamic analysis (energy and exergy analysis) of an operational combined cycle for electricity generation, incorporating a biomass gasification system utilizing wood chips as the biomass in a cofiring approach. The primary objectives are to enhance energy generation and reduce CO2 emissions. A sensitivity analysis of the combined power plant was performed to determine the main and interaction effects on output variables. The plant's thermal efficiency and carbon dioxide emission rate are also analyzed. An optimization procedure was proposed using two approaches: a multi-objective optimization (Pareto frontier) to minimize carbon dioxide emissions and maximize power generation, and three single-objective optimizations focused on replacing natural gas with syngas. The results demonstrated that the most influential parameters for total energy generation are fuel and steam flow rates, gas turbine compression ratio, and steam turbine outlet pressure and inlet temperature. Replacing natural gas with syngas increased fuel mixture temperatures, necessitating higher atmospheric air flow rates to prevent excessive gas turbine inlet temperatures. Additionally, this substitution improved the potential for thermal recovery. The optimal operating condition identified through single-objective optimization increased total power generation by 14.5 %. Moreover, the optimization procedure revealed that higher syngas proportions in the fuel mixture led to lower carbon dioxide emission rates. For cases where the gas-to-mass ratio (GMR) values were 0.34 and 0.32, the corresponding carbon dioxide emission rates were 0.58 kg/kWh and 0.57 kg/kWh, respectively.
Keywords: Biomass gasification; Combined cycle; Optimization; Renewable energy; Sensitivity analysis; Thermodynamic analysis